Effects of growth factors and receptor blockade on gastrointestinal cancer. Issue 8 (9th July 2004) - Playford, R J; Wassan, H; Ghosh, S
Abstract : The advent of recombinant peptide technology offers the potential to use one or several peptides to treat a variety of gastrointestinal conditions. However, although cell culture and animal models have shown proof of concept, we are still at a relatively early stage in translating their use to standard clinical practice. Similarly, peptide and non-peptide antagonists of growth factor receptors show great potential as novel antichemotherapy agents. However, their actual place in clinical practice has yet to be established.